2019
DOI: 10.3906/mat-1907-41
|View full text |Cite
|
Sign up to set email alerts
|

Study on the q-analogue of a certain family of linear operators

Abstract: In this paper, we introduce the q-analogue of a certain family of linear operators in geometric function theory. Our main purpose is to define some subclasses of analytic functions by means of the q-analogue of linear operators and investigate various inclusion relationships with integral preserving properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…The class S * q of q-starlike functions was introduced in [4] and has been studied in [7,8,9,10,12,13,14,15,16,20,21,22].…”
Section: Introduction and Preliminary Resultsmentioning
confidence: 99%
“…The class S * q of q-starlike functions was introduced in [4] and has been studied in [7,8,9,10,12,13,14,15,16,20,21,22].…”
Section: Introduction and Preliminary Resultsmentioning
confidence: 99%
“…For example, the convolution theory, enable us to investigate various properties of analytic functions. Due to the large range of applications of q-calculus and the importance of q-operators instead of regular operators, many researchers have explored q-calculus in depth, such as, Kanas and Reducanu [9], Muhammad and Sokol [10] and Noor et al [11][12][13][14][15]. Also in [1-5, 9, 16-22], Ahmad et al see also [21], have used the q-derivative operator to define a new subclass q-meromorphic starlike functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in [18], Shah and Noor introduced the q-analogue of Srivastava-Attiya operator J s q,b : A → A by…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that, if co-analytic part of f = h + g is identically zero, then the modified q-Srivastava-Attiya operator defined by (1.4) turn out to be the q-Srivastava-Attiya operator introduced in [18].…”
Section: Introductionmentioning
confidence: 99%